2020
DOI: 10.1111/joa.13321
|View full text |Cite
|
Sign up to set email alerts
|

Damage to the human lumbar cartilage endplate and its clinical implications

Abstract: The cartilaginous endplate (CEP) is a thin layer of hyaline cartilage, and plays an important role in the diffusion of nutrients into the intervertebral discs. Its damage may seriously affect the disc degeneration, and result in low back pain (LBP). However, the structural features of damaged CEPs have not been well characterized, and this hinders our understanding of the etiology of disc degeneration and pain. To present the How to cite this article: Huang B, Liu J, Wei X, et al. Damage to the human lumbar ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…36 Calcification is considered the hallmark of CEP degeneration, and the NP has been shown to be the primary area affected by CEP degeneration. 37 However, MRI of the CEP is challenging due to its physiological thickness of only approximately 0.6 mm; and ultrashort echo time (UTE) imaging is considered a promising technique. 38 Kim et al reported that three-dimensional UTE MRI could be used to depict CEP and CEP abnormalities, which might be associated with the severity of disk degeneration on T2-weighted spin-echo MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Calcification is considered the hallmark of CEP degeneration, and the NP has been shown to be the primary area affected by CEP degeneration. 37 However, MRI of the CEP is challenging due to its physiological thickness of only approximately 0.6 mm; and ultrashort echo time (UTE) imaging is considered a promising technique. 38 Kim et al reported that three-dimensional UTE MRI could be used to depict CEP and CEP abnormalities, which might be associated with the severity of disk degeneration on T2-weighted spin-echo MRI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that when osteoporosis leads to changes in the microenvironment of the vertebral body, the morphology of the CEPs of the vertebral body is first altered, which in turn causes nutritional disorders and degeneration of the IVD 36 . Calcification is considered the hallmark of CEP degeneration, and the NP has been shown to be the primary area affected by CEP degeneration 37 . However, MRI of the CEP is challenging due to its physiological thickness of only approximately 0.6 mm; and ultrashort echo time (UTE) imaging is considered a promising technique 38 .…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the main reasons leading to the low short‐term fusion rate in patients with MCs might be inflammatory factors and a reduced blood supply in the fusion area. Inflammatory factors such as TNF‐α can be produced in the intervertebral space by low‐toxicity infection of the intervertebral space, autoimmune reactions caused by exposure to the nucleus pulposus and intraoperative curettage of the endplate cartilage 24,25 . TNF‐α inhibits the osteogenic differentiation of mesenchymal stem cells by activating the NF‐κB pathway or Notch receptors, 7,26 which may lead to trabecular bone formation between the implanted bone and vertebral bone.…”
Section: Discussionmentioning
confidence: 99%
“…Bony endplate (BEP) and cartilaginous endplate (CEP) are the two different layers of EP [ 7 , 8 ]. CEP contains vascular channels when in infancy and early childhood, while the vessels are atretic before adolescence, leaving blood circulation in the BEP only and insufficient nutrition for the disc [ [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%